The Characteristics or Preparation? the Most Influential Factor in Speaking Performance for ESP Students - Ajiza, Masrurotul (Pusdikra-Publishing.com, 2025)
This study aimed to explore the most influential factor in the speaking performance of students in English for Specific Purposes (ESP) classes. Interestingly, the participants had never previously received specific instruction or materials related to speaking performance. Despite this, their speaking abilities varied considerably. The study involved 25 students from the Civil Engineering department, most of whom are members of Generation Z and are naturally familiar with using technology to support their learning. This study is urgently needed to raise students’ awareness that relying solely on personal characteristics, particularly introverted tendencies, may not be sufficient to achieve successful speaking performance in public settings. This research sought to answer three key questions: (1) What student characteristics most influence the speaking performance of ESP students in engineering classes? (2) How does students' preparation before speaking activities impact their speaking performance? and (3) Which factor has a greater influence on ESP students' speaking performance: personal characteristics or preparation? Data were collected through class observation. The findings indicated that extroverted characteristics appeared to help students manage their speaking performance more confidently. However, despite showing fluency, many students struggled to develop communication depth. This study was limited to one ESP class in the Civil Engineering department. Future studies are encouraged to explore this topic in different fields, across larger samples, and with students who have varying levels of prior exposure to speaking instruction.